Evolution of Gene Structural Complexity: An Alternative-Splicing-Based Model Accounts for Intron-Containing Retrogenes . Issue 1 (11th February 2014) - Zhang, Chengjun; Gschwend, Andrea R.; Ouyang, Yidan; Long, Manyuan
Abstract : An alternative-splicing-based model explains the formation of retrogenes that retained the parental intron structure and indicates that plants have a much higher percentage of this kind of complex retrogene than animals . Abstract: The structure of eukaryotic genes evolves extensively by intron loss or gain. Previous studies have revealed two models for gene structure evolution through the loss of introns: RNA-based gene conversion, dubbed the Fink model and retroposition model. However, retrogenes that experienced both intron loss and intron-retaining events have been ignored; evolutionary processes responsible for the variation in complex exon-intron structure were unknown. We detected hundreds of retroduplication-derived genes in human ( Homo sapiens ), fly ( Drosophila melanogaster ), rice ( Oryza sativa ), and Arabidopsis ( Arabidopsis thaliana ) and categorized them either as duplicated genes that have all introns lost or as duplicated genes that have at least lost one and retained one intron compared with the parental copy (intron-retaining [IR ] type). Our new model attributes intron retention alternative splicing to the generation of these IR -type gene pairs. We presented 25 parental genes that have an intron retention isoform and have retained introns in the same locations in the IR -type duplicate genes, which directly support our hypothesis. Our alternative-splicing-based model in conjunction with the retroposition and Fink models can explain the IR -type gene observed. We discovered a greater percentage of IR -type genes in plants than in animals, which may be due to the abundance of intron retention cases in plants. Given the prevalence of intron retention in plants, this new model gives a support that plant genomes have very complex gene structures.